Evaluation of heat flow anomalies and hydrocarbon accumulation in IB field, Malaysia - Yusof, M.A.M. (International Multidisciplinary Scientific Geoconference, 2014)
Studies of heat flow anomalies have been conducted in the hydrocarbon field to determine types of heat flow mechanisms namely conduction, radiation and convection. A heat flow anomaly can be detected if the calculated value varies in huge difference compared to the normal heat flow in that particular area. In a sedimentary basin, two major heats transmission mechanisms are conduction and convection. Conductive heat flow usually related to heat energy transferred from deeper crust and the presence of stagnant fluid while the convective heat flow often allied with the existence of subsurface fluid flow in a field. The research has been carried out to determine the relationship of heat flow anomalies with hydrocarbon accumulation. To obtain the vertical profiles of thermal conductivity, formation temperature and heat flow of that area, data from four wells in a hydrocarbon field in South China Sea, Malaysia have been used. The conductive heat is identified when the thermal conductivity line is inversely proportional to the temperature gradient while convective heat occurred when both lines are proportional to each other. The vertical profiles were compared with the structural cross section to correlate with the existence of fluid in the field. Apparently, the result showed the presence of thick oil zone in the reservoir where convective heat has been identified. The results showed that the presence of thick oil bearing zone in the reservoir where conductive heat has been identified. Besides, the conductive heat is also found in constant heat flow profiles. In conclusion, the thermal profiles obtained are really helpful in order to detect heat flow anomalies in vertical well profiles. The anomalies were also understood to be allied with the hydrocarbon accumulation in the basin. Â© SGEM2014. All Rights Reserved.